Life in a black community : striving for equal citizenship in Annapolis, Maryland, 1902-1952 - Jopling, Hannah, 1942- (Lexington Books, 2015)
Life in a Black Community details and explores the Jim Crow era in Annapolis, Maryland. It recounts the tactics blacks used to gain equal rights, details the methods whites employed to deny or curtail their rights, and explores a range of survival and advancement strategies used by black families.